ChemInform Abstract: A Photo‐Induced C—C Bond Formation Methodology to Construct Tetrahydrofluorenones and Their Related Structures. Issue 27 (16th June 2016) - Cai, Shujun; Xiao, Zheming; Ou, Jinjie; Shi, Yingbo; Gao, Shuanhu
Abstract: A previously reported photo‐Nazarov reaction is used for preparation of tetrahydrofluorenones and higher ring homologs thereof.